Anticancer effect of myristicin on hepatic carcinoma and related molecular mechanism - Hailan Bao; Qi Muge (Taylor & Francis Group, 2021)
Context Myristicin is a natural active compound that has inflammatory, antimicrobial and anti-proliferative properties. Yet, its effect on hepatic carcinoma has not been investigated. Objective To explore the role and related molecular mechanism of myristicin in hepatic carcinoma in vitro. Materials and methods Human hepatic carcinoma cell lines (Huh-7 and HCCLM3 cells) were treated with different concentrations of myristicin (0.5, 1 and 5 mM) for 24, 48 and 72 h. Then, (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium assay (MTT), flow cytometer (FCM) analysis and transwell assay were performed to determine cell proliferation, apoptosis and migration/invasion, respectively. Protein levels of B-cell lymphoma-2 (Bcl-2), Bcl-2 associated X (Bax), E-cadherin, N-cadherin and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signalling pathway-related proteins were detected using Western blot assay. Gene expression was determined using quantitative real time-polymerase chain reaction (qRT-PCR). Results Myristicin inhibited cell proliferation and induced apoptosis in Huh-7 and HCCLM3 cells; suppressed cell migration and invasion ability, and increased E-cadherin expression and decreased N-cadherin expression, thereby inhibiting epithelial-mesenchymal transition (EMT). Finally, the findings indicated that myristicin decreased phosphorylated (p)-mTOR and p-AKT expression at the protein level. Discussion and conclusions Myristicin exerts an efficient therapeutic effect on hepatic carcinoma by suppressing PI3K/Akt/mTOR signalling pathway; thus, it may be used as a new potential drug for hepatic carcinoma treatment.